Fenomena Fatherless Fungsional dalam Perspektif Maqāṣid al-Usrah: Studi Pandangan Ulama di Desa Ciawi Bojonggambir - Alfi Nurhidayah Ginanjar; Mufidah; Burhanuddin Susmanto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Functional fatherlessness has emerged as a contemporary family issue characterized by the physical presence of fathers within the family while lacking emotional involvement, educational roles, and optimal caregiving functions. This condition potentially affects family resilience, particularly in the aspects of religious education, family relationships, and children’s character development. This study aims to analyze the views of Islamic scholars in Ciawi Bojonggambir Village, Tasikmalaya Regency, regarding the phenomenon of functional fatherlessness and its impact on family resilience from the perspective of Jamāl al-Dīn ‘Aṭiyyah’s Maqāṣid al-Usrah. The research employed an empirical juridical approach using descriptive-analytical qualitative methods. Primary data were obtained through interviews with local Islamic scholars, while secondary data were collected from Islamic family law literature, Jamāl al-Dīn ‘Aṭiyyah’s works, academic journals, and other supporting documents. The findings reveal that Islamic scholars perceive functional fatherlessness as a manifestation of the weakening of the qawwāmah function within the family, which affects all dimensions of Maqāṣid al-Usrah, including family relations, preservation of lineage, family tranquility, religious education, family institutional structure, and financial balance